Green Synthesis of Carbon Dot Weak Gel from Pear Juice: Optical Properties and Sensing Application. Issue 29 (1st August 2018) - Mondal, Jayanta; Srivastava, Suneel Kumar
Abstract: Herein, we report for the first time a low‐cost and eco‐friendly carbon dot weak gel (CDWG) in the absence of any gelling agent from a pear juice as a green precursor. Our findings showed that the volatile nature of acetone, basic media, and cellulose content in pear juice played key roles in the formation of CDWG. This fabrication strategy of CDWG from a green precursor in absence of gelling agent could be more advantageous over CD‐hybrids gel. Further, the fabricated gel exhibited excitation dependent red shifted multicolor (blue‐green‐yellow‐orange) emission due to the presence of characteristic hydrophilic surface in CDs. The other unique feature of the work involved utilization of inherent fluorescent property of CDs in establishing optical interaction between 0D CDWG and 2D reduced graphene oxide (G) and graphene oxide (GO). It may be concluded that the quenching is mainly guided by the electron rich CDs and electron acceptance ability, large specific surface area of G and GO. It is also interesting to note that the introducing of gel property in CDs exhibit improved sensing efficiency and limit of detection of CDWG (1.5 μg ml −1 ) for G. Further, such optical sensing could be beneficial for the fabrication of optoelectronics, photovoltaic devices and sensing of bio‐molecules and metal ions. Abstract : Green route has been used to synthesize carbon dot weak gel followed by application in optical sensing of graphene oxide and reduced graphene oxide.